Perioperative and postoperative morbidity following open hemorrhoidectomy - Alam, M. Morshed; Rahman, M. Shafiqur; Ferdaus, M. Ashek M.; Antara, Fateha Y. (International Surgery Journal, 2025)
Background: Open hemorrhoidectomy (Milligan-Morgan technique) remains a standard procedure for advanced hemorrhoidal disease, particularly in low- and middle-income countries. This study evaluated perioperative and postoperative morbidity, recovery patterns, and cost-effectiveness in a Bangladeshi cohort. Methods: A prospective observational study was conducted on 65 patients undergoing open hemorrhoidectomy for grade III and IV hemorrhoids. Data were collected on demographics, intraoperative bleeding, postoperative pain (VAS score), complications, hospital stay, recovery time, and total cost. Descriptive statistics were applied. Results: The mean age was 40.52±10.75 years, with a male predominance (56.9%). Grade IV hemorrhoids were present in 55.4% of cases. Intraoperative bleeding was minimal in 95% of patients. Postoperative pain was significant, with 80% experiencing moderate-to-worst pain in the first 24 hours. Urinary retention occurred in 40%, while reactionary and secondary hemorrhage were noted in 6.2% and 3.1%, respectively. The mean hospital stay was 7.12±2.58 days, and the mean time to return to normal activities was 14.29±3.57 days. Treatment costs were below 10,000 BDT for 98.5% of patients. Conclusions: Open hemorrhoidectomy is a cost-effective procedure with minimal intraoperative morbidity but significant postoperative pain and delayed recovery. Tailored perioperative care protocols could further enhance recovery and improve patient experience.